STUDY REGARDING THE DESTABILIZATION OF STABLE EMULSIONS FROM SUPLAC AREA - Ghetiu, Iuliana Veronica; Stan, Ioana Gabriela; Popescu, Maria Georgeta (Scientific Study & Research. Chemistry & Chemical Engineering, Biotechnology, Food Industry, 2016)
Emulsions from the wells in the Suplac area create great difficulties in removing water due to their specifications. A complex study was conducted in order to eliminate water from emulsions using alkaline-surfactants. The choice of surfactant was made after the chromatographic SARA analysis of emulsions and the determination of their physical properties: density, viscosity, organic acidity. The samples were taken from two wells in the Suplac area. In the case of samples from A well the variation of density is 907 - 955 kg.m^sup -3^ for crude oil and 928 - 970 kg.m^sup -3^ for emulsion, while the rheological behavior of the emulsion varies between 0.680 to 0.995 Pa.s at a temperature of 25 °C and between 0.049 to 0.328 Pa.s at a temperature of 80 °C. For samples from B well the variation of density is 855 - 905 kg.m^sup -3^ for crude oil and 939 - 970 kg.m^sup -3^ for emulsion, while the rheological behavior of the emulsion varies between 0.149 to 0.797 Pa.s at a temperature of 25 °C and between 0.014 to 0.397 Pa.s at a temperature of 80 °C. The justification for choosing R - DP surfactant like reagent was based on laboratory tests which showed a maximum efficiency at 80 °C (95.69 for B and 98.75 % for A).